Continuous casting method for steel
Patent Information
- Application Number
- JP2021084428
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-05-19
- Publication Date
- 2025-02-20
- Estimated Expiration
- 2041-05-19
AI Technical Summary
【0014】 本発明によれば、亜包晶鋼などのδ-γ変態が生じうる組成の鋼を製造する際に、不均一凝固による縦割れを防止するとともに、鋳造時における横方向のひび割れを防止できる鋼の連続鋳造方法を提供することができる。
Smart Images

Figure 0007633513000003 
Figure 0007633513000001 
Figure 0007633513000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for continuous casting of steel, such as hypoperitectic steel, to prevent longitudinal and transverse cracks when producing the steel. [Background technology]
[0002] In the continuous casting of molten metal, mold powder for continuous casting is supplied so as to cover the surface of the molten metal in the mold. Hereinafter, such mold powder for continuous casting is simply called "mold powder". The mold powder supplied into the mold forms a molten layer on the surface of the molten metal by heating from the molten metal, and the molten mold powder flows from the meniscus of the molten steel along the inner wall of the mold into the gap between the mold and the solidified shell, forming a film.
[0003] The mold powder is required to have the following properties for continuous casting of molten metal: First, the molten mold powder layer formed by melting the mold powder on the surface of the molten steel and the unmelted mold powder layer on top of that cover the surface of the molten steel, blocking contact with air, thereby preventing re-oxidation of the molten steel and providing the effect of retaining heat. Secondly, since the molten mold powder needs to flow between the mold and the solidified shell and act as a lubricant, it is required that an appropriate amount of mold powder is constantly supplied and that the melting speed is such that the molten mold powder pool has an appropriate thickness in accordance with the mold powder consumption rate. Third, it is required that the molten mold powder layer absorbs nonmetallic inclusions that rise to the surface in the molten steel, and that the change in the physical properties of the molten mold powder (viscosity, melting temperature, solidification temperature, etc.) caused by absorbing the nonmetallic inclusions is minimal. Fourth, the molten mold powder flows into the gap between the mold and the solidified shell to form a uniform powder film. The powder film acts as a lubricant between the mold and the solidified shell, and depending on the properties of the steel being cast, the slow cooling properties of the solidified shell may be required. Fifth, the molten mold powder must have appropriate viscosity and interfacial tension so that the molten mold powder is not entrained in the molten steel.
[0004] Here, when casting molten steel with a composition in which δ-γ transformation can occur, such as ordinary steel with a C concentration of 0.07% to 0.18% by mass (hereinafter referred to as hypoperitectic steel), delta ferrite is formed in the early stages of solidification of the molten steel, and then, when further cooled, the delta ferrite transforms into austenite. When delta ferrite transforms into austenite, contraction occurs, which makes it easy for vertical cracks to occur due to uneven solidification. In order to prevent such vertical cracks, Patent Document 1 discloses a casting method that uses a mold powder in which cuspidine (3CaO·2SiO2·CaF2) precipitates in a film, thereby reducing the amount of heat dissipated to the mold. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6515394 Summary of the Invention [Problem to be solved by the invention]
[0006] However, although the use of the molding powder described in Patent Document 1 can prevent vertical cracks, horizontal cracks may occur during casting.
[0007] In view of the above-mentioned problems, an object of the present invention is to provide a method for continuous casting of steel, which can prevent vertical cracks due to non-uniform solidification and horizontal cracks during casting when producing steel having a composition in which the δ-γ transformation can occur. [Means for solving the problem]
[0008] The present inventors first investigated in what cases transverse cracks occur during casting of steels with compositions in which δ-γ transformation can occur, such as hypoperitectic steels. As a result, it was found that such cracks do not occur when mold powders with low slow cooling ability are used, and further that such cracks occur when a mold equipped with an electromagnetic stirrer, which has been widely used in recent years, is used.
[0009] Therefore, the inventors further investigated the cause of such cracking. First, when the surface layer of the slab when cracks occurred was observed, it was found that coarse austenite grains were formed, and cracks occurred at the grain boundaries of the austenite grains. The coarsening of austenite grains occurs when the surface of the slab is held at high temperatures for a long time after the initial solidification region. Normally, this phenomenon can be avoided by adjusting the water volume conditions for secondary cooling, but it was found that the austenite grains coarsened and transverse cracks occurred regardless of the secondary cooling conditions.
[0010] From the above results, the inventors presumed that the coarsening of austenite grains is caused by the cooling conditions in the lower part of the mold. A mold equipped with an electromagnetic stirring device is usually made of a copper plate material with low electrical and thermal conductivity. In addition, in a mold equipped with an electromagnetic stirring device, the casting direction of the mold copper plate is longer than that of a normal mold in order to secure space for the electromagnetic stirring device, and in the case of a mold equipped with an electromagnetic brake device, the casting direction of the mold copper plate is even longer. Furthermore, when the mold powder described in Patent Document 1 is used, the amount of heat removed to the mold is reduced, so that vertical cracks can be prevented by slow cooling in the upper part of the mold, but the amount of heat removed is also reduced even in the lower part of the mold, so that cooling in the austenite region becomes slow.
[0011] As described above, it was found that because mold powder and copper plates that are difficult to remove heat from are used, and the casting direction of the mold is long, the slab enters the secondary cooling zone with high cooling capacity late, and coarse austenite grains grow. From the above results, the inventors have found conditions for slow cooling in the upper part of the mold while ensuring cooling capacity in the lower part of the mold in order to prevent both vertical and horizontal cracks, and have arrived at the present invention.
[0012] The present invention is as follows. (1) A method for continuous casting of steel, comprising the steps of pouring molten steel having a composition capable of causing a δ-γ transformation into a mold having a mold copper plate having an electrical conductivity of 70 IACS% or less, supplying mold powder, and continuously casting the molten steel while stirring the molten steel using an electromagnetic stirrer so that the average molten steel flow velocity at a position 50 mm below the molten steel surface and 5 mm from the long side copper plate is 5 cm / s or more over the entire width, The mold powder is In mass%, Na2O: 6% or more, Li2O: 0.5% or more, and F: 15% or less, Contains The basicity (T.CaO / SiO2) is 1.1 to 1.7, The viscosity at 1300℃ is 0.20 Pa s or less, The main crystals that precipitate when cooled from the molten state at 5℃ / min are cuspidine. and the second crystal is NaF or Nepheline 2. A method for continuous casting of steel comprising the steps of:
[0013] (2) 2. The method for continuous casting of steel according to claim 1, wherein the mold further comprises an electromagnetic brake device, and the distance from the surface of the molten steel in the mold to the bottom of the mold is 800 mm or more. Effect of the Invention
[0014] According to the present invention, there is provided a continuous casting method for steel that can prevent vertical cracks due to non-uniform solidification and horizontal cracks during casting when producing steel having a composition in which the δ-γ transformation can occur, such as hypoperitectic steel. [Brief description of the drawings]
[0015] [Figure 1] FIG. 11 is a diagram showing the relationship between the mold length and the number of cracks in the second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present invention will be described. In this embodiment, in the continuous casting method of steel, a mold powder is used that has cooling ability in the lower part of the mold while ensuring a certain degree of heat extraction in the upper part of the mold. Specifically, the cooling ability in the lower part of the mold is ensured by using a mold powder that has a slow cooling ability, does not crystallize excessively, and leaves a liquid phase mainly composed of Si-Na-Li-FO after crystal precipitation. On the other hand, since the slow cooling in the upper part of the mold is insufficient with only the mold powder, the prevention of uneven solidification in the upper part of the mold is realized by providing a smooth molten steel flow by electromagnetic stirring in addition to the slow cooling by the mold powder. Furthermore, a material with low electrical conductivity is used for the copper plate of the mold so that the unevenness suppression effect by electromagnetic stirring can be fully enjoyed.
[0017] First, the conditions of the mold powder used in this embodiment will be described. First, as conditions that allow slow cooling in the upper part of the mold and strong cooling in the lower part of the mold, while allowing primary crystal cuspidine to precipitate stably and abundantly, the remainder after cuspidine precipitation is made to have a composition that is difficult to solidify, and heat removal in the lower part of the mold is promoted. In order to make the remainder after cuspidine precipitation difficult to solidify in this way, the composition is made to contain Li2O and sufficient Na and F.
[0018] Since Li has a small atomic radius, it hardly forms crystals, and as a result, Li2O has the effect of improving the cooling ability at the bottom of the mold. In addition, since Li2O has a low molecular weight, it is effective even when it is contained in small amounts. On the other hand, if it contains sufficient Na and F, the remaining F will either precipitate as NaF or remain in the glass or liquid phase. In addition, since NaF has a low melting point, it can be considered to be essentially equivalent to the glass or liquid phase in the mold.
[0019] However, it is necessary to avoid F being fixed as CaF2, which has a relatively high melting point. In other words, the crystals precipitated in the molding powder used in this embodiment are such that the main crystals (first crystals) are cuspidine, and the second most abundant crystals (second crystals) are crystals other than CaF2.
[0020] Here, the main crystals that precipitate when the molten mold powder solidifies will be described. The main crystals are the crystals that precipitate most when the target mold powder is melted at 1300°C to 1400°C and then solidified from the molten state at a cooling rate of 5°C / min. The definition of the main crystals is a crystal whose peak intensity is 1.5 times or more than other crystals when the solidified mold powder is subjected to X-ray diffraction analysis. When the crystals are arranged in order of peak intensity, if the peak intensity ratio between No. 1 and No. 2 is 1.5 times or more, only the No. 1 crystal is the main crystal. If the peak intensity ratio between No. 1 and No. 2 is less than 1.5 times, and the peak intensity ratio between No. 2 and No. 3 is 1.5 times or more, the No. 1 and No. 2 crystals are the main crystals. The No. 2 crystal can be said to be a crystal precipitated by secondary crystallization.
[0021] Thus, it is important that the liquid or glass phase remaining after cuspidine precipitation contains a large amount of Si-Na-Li-FO.
[0022] Next, the components contained in the mold powder will be described. In the following, unless otherwise specified, "%" simply means "mass %." [T.CaO / SiO2] Both CaO and SiO2 are the main components of the mold powder, and the basicity (T.CaO / SiO2) is set to 1.1 to 1.7. If the basicity is less than 1.1, cuspidine does not precipitate sufficiently, so heat transfer at the upper part of the mold increases, and vertical cracks occur. On the other hand, if the basicity exceeds 1.7, the amount of CaO becomes too large, so that the liquid phase or glass phase contains a large amount of Ca. In this case, crystals with a relatively high melting point containing CaF2 or CaO are further precipitated, and the cooling ability at the lower part of the mold decreases.
[0023] [LiO] As mentioned above, Li2O has the effect of improving the cooling ability at the bottom of the mold. Therefore, Li2O is contained in an amount of 0.5% or more. Although there is no particular upper limit for the Li2O content, since Li2O is expensive, it is preferable that the content be 5.0% or less.
[0024] [Na2O] As mentioned above, Na in Na2O precipitates as NaF, which has a low melting point, and can be regarded as substantially equivalent to a glass phase or liquid phase. Therefore, Na2O is to be contained in an amount of 6% or more. Although there is no particular upper limit for the Na2O content, if there is too much Na2O, the mold powder becomes easily sintered, and the resulting sintered body (slag rim) has a negative effect on operation, so it is preferable that the content be 12% or less.
[0025] [F] F is an element necessary for precipitating as NaF, but if it is contained in excess, CaF2 is likely to precipitate, so the content is set to 15% or less. In this embodiment, since the first crystal is cuspidine, the F content is determined to some extent, but it is preferable to contain 5% or more.
[0026] [Al2O3, MgO, SrO] These compounds are not essential in the mold powder, but while Al2O3 has the effect of increasing viscosity, if it is added in excess it can cause high melting point crystals to precipitate, so it is preferable to include 2 to 8%. MgO is sometimes used to lower the solidification temperature, but it can also cause high melting point crystals to precipitate, so it is preferable to have a content of 5% or less. In addition, SrO is sometimes used to adjust the amount of cuspidine precipitation, but if used in excess, cuspidine will not precipitate sufficiently, so it is preferable to have a content of 5% or less.
[0027] Next, other characteristics of the mold powder used in this embodiment will be described. The solidification temperature of the mold powder is not particularly specified, but if it is too high, there is a concern of poor lubrication, and if it is too low, there is a concern of vertical cracking, so it is preferably 1100°C or more and 1200°C or less. In addition, the viscosity of the mold powder is not particularly specified, but when the main crystal is cuspidine, the viscosity at 1300°C is usually 0.20 Pa·s or less.
[0028] Next, the conditions other than the mold powder in the method for continuous casting of steel in this embodiment will be described. As described above, a copper plate with low electrical conductivity is used for the mold. Specifically, a material with electrical conductivity of 70 IACS (International Annealed Copper Standard)% or less at room temperature is used. Here, the internationally adopted annealed standard soft copper (volume resistivity: 1.7241×10 -2 The electrical conductivity of the copper plate is defined as 100 IACS%. If a copper plate with an electrical conductivity of more than 70 IACS% is used, the initial solidification region will be cooled strongly, causing vertical cracks. There is no lower limit for the electrical conductivity of the copper plate, but if the electrical conductivity is too low, poor solidification is likely to occur, so it is preferable to make it 40 IACS% or higher.
[0029] In this embodiment, when molten steel is poured into the mold, electromagnetic stirring is performed using an electromagnetic stirrer to provide a smooth flow of molten steel and prevent uneven solidification. The stirring conditions are such that the average molten steel flow velocity at a position 50 mm below the molten steel surface and 5 mm from the long side copper plate is 5 cm / s or more across the entire width. If the average molten steel flow velocity at this position is less than 5 cm / s, the molten steel is not stirred sufficiently, causing uneven solidification, which results in vertical cracks. On the other hand, there is no particular upper limit for the average molten steel flow velocity at this position, but since a flow velocity that is too high may cause mold powder to be entrained in the molten steel, it is preferable that the average molten steel flow velocity at this position is 20 cm / s or less.
[0030] In addition, a mold equipped with not only an electromagnetic stirring device but also an electromagnetic brake device may be used. When an electromagnetic brake device is installed in the mold, a large amount of space is required, and the mold becomes longer accordingly. Therefore, the longer the distance from the molten steel surface to the bottom end of the mold, the greater the degree of freedom in designing the installation of the electromagnetic brake device, which is a desirable form. In addition, in the continuous casting method of this embodiment, the longer the distance from the molten steel surface to the bottom end of the mold, the more significant the difference in effect. From the above points, when a mold equipped with an electromagnetic brake device is used, it is preferable to ensure that the distance from the molten steel surface in the mold to the bottom end of the mold is 800 mm or more.
[0031] As described above, in this embodiment, by using a mold powder with predetermined conditions, using a copper plate of low electrical conductivity for the mold, and further controlling the flow rate of molten steel, it is possible to prevent vertical cracks as well as horizontal cracks in continuous casting of steel having a composition in which the δ-γ transformation can occur, such as hypoperitectic steel. EXAMPLES
[0032] An embodiment of the present invention will be described. The conditions in the embodiment are one example of conditions adopted to confirm the feasibility and effects of the present invention, and the present invention is not limited to this one example of conditions. The present invention can adopt various conditions as long as they do not deviate from the gist of the present invention and achieve the object of the present invention.
[0033] (First embodiment) More than 150 t of molten steel containing 0.09 to 0.12% C by mass was prepared and poured into a mold equipped with an electromagnetic stirrer, with a width of 1300 mm and a distance of 700 mm from the molten steel surface to the bottom of the mold, and mold powders of samples A to G and L to P shown in Table 1 were added in each example. After secondary cooling, slabs with a thickness of 250 mm were produced. The electrical conductivity and stirring flow rate of the copper plate of the mold (average molten steel flow rate at a position 50 mm below the molten steel surface and 5 mm from the long side copper plate) were as shown in Table 2, and the stirring flow rate was measured as the average molten steel flow rate at a position 50 mm below the molten steel surface and 5 mm from the long side copper plate.
[0034] Vertical and horizontal cracks were observed in 150 ton slabs, and the presence or absence of each type of crack was evaluated.
[0035] [Table 1]
[0036] [Table 2]
[0037] In Examples 1 to 7 in Table 2, no vertical or horizontal cracks were observed. On the other hand, in Comparative Examples 1, the basicity was too low, so the main crystals were cuspidine, but the precipitation was insufficient. As a result, vertical cracks occurred. In Comparative Example 2, the basicity was too high, so crystals with a high melting point were generated, and the cooling ability at the bottom of the mold decreased. As a result, horizontal cracks occurred.
[0038] In Comparative Example 3, since Na2O was insufficient, the precipitation of NaF, which has a low melting point, was small, and the cooling ability at the bottom of the mold was reduced. As a result, horizontal cracks occurred. In Comparative Example 4, since Li2O was insufficient, the cooling ability at the bottom of the mold was reduced. As a result, horizontal cracks occurred. In Comparative Example 5, since F was excessively contained, CaF2, which has a high melting point, was precipitated as the second crystal, and the cooling ability at the bottom of the mold was reduced. As a result, horizontal cracks occurred.
[0039] In Comparative Examples 6 and 7, the stirring flow rate was too slow, which caused uneven solidification, resulting in vertical cracks. In Comparative Examples 8 and 9, the conductivity of the copper plate was too high, which caused strong cooling in the initial solidification region. As a result, vertical cracks were generated.
[0040] (Second Example) The same molten steel as in the first embodiment was prepared and poured into molds equipped with an electromagnetic stirring device and an electromagnetic brake layer device, each with a mold width of 1300 mm and different distances from the molten steel surface to the bottom of the mold, and the mold powders of samples A and M shown in Table 1 were added in each example. After secondary cooling, a slab with a thickness of 250 mm was produced. At this time, the conductivity of the copper plate of the mold was 50IACS%, and the stirring flow rate was 12 cm / s. In addition, a maximum of 3000 gauss was applied to the center of the mold thickness by the electromagnetic brake device.
[0041] Transverse cracks were observed in units of 300 ton slabs, and the number of cracks per unit length was evaluated.
[0042] Figure 1 is a diagram showing the relationship between the distance from the molten metal surface to the bottom end of the mold and the number of cracks. As shown in Figure 1, when comparing the case where mold powder sample A was used with the case where mold powder sample M was used, there were no cracks or the number of cracks was extremely small in sample A. In addition, the difference was remarkable when the distance from the molten metal surface to the bottom end of the mold was 800 mm or more.
Claims
1. A method for continuous casting of steel, comprising the steps of pouring molten steel having a composition capable of causing δ-γ transformation into a mold having a mold copper plate having an electrical conductivity of 70 IACS% or less, supplying mold powder, and continuously casting the molten steel while stirring the molten steel using an electromagnetic stirrer so that the average molten steel flow velocity at a position 50 mm below the molten steel surface and 5 mm from the long side copper plate is 5 cm / s or more over the entire width, The mold powder is In mass percent, Na 2 O: 6% or more, Li 2 O: 0.5% or more, and F: 15% or less, Contains Basicity (T.CaO / SiO 2 ) is 1.1 or more and 1.7 or less, The viscosity at 1300°C is 0.20 Pa s or less, 1. A method for continuous casting of steel, characterized in that when the steel is cooled from a molten state at a rate of 5° C. / min, the main crystals which precipitate are cuspidine and the secondary crystals are NaF or nepheline.
2. 2. The method for continuous casting of steel according to claim 1, wherein the mold further comprises an electromagnetic brake device, and the distance from the surface of the molten steel in the mold to the bottom end of the mold is 800 mm or more.
Citation Information
Patent Citations
Fluoride-free mold powder for low-carbon steel
CN103317111A
Continuous casting method of steel superior in cleanness property
JP2000280051A
Method of manufacturing continuous cast slab
JP2002001501A
Mold powder for continuously casting steel and continuous casting method
JP2003290888A
Product having improved zinc corrosion resistance
JP2006212662A